Perlindungan Kreditur Atas Pailit Yang Diajukan Debitur Dalam Proses Peninjauan Kembali Di Pengadilan Niaga - Ronald Saija (Faculty of Law, Universitas Pattimura, 2018)
Legislation Number 34 of 2007 concerning Bankruptcy and Postponement of Obligations of Debt Payments is not fully complete in order to protect the rights of creditors, in connection with the dispute of PT. Golden Adishoes has no clarity about repayment in full if it turns out that the debtor's assets are insolvent is not enough to pay all of his debts, indirectly the creditor is required to accept the fact that all of his debts will not be repaid in full by bankrupt debtors without any actions and what solutions can be made by the creditor before the bankruptcy application is filed by the bankrupt debtor to the Commercial Court.